New perspective for biorefining cereals. (26th November 2013) - Abecassis, Joel; de Vries, Huug; Rouau, Xavier
Abstract We present a novel approach for the valorization of cereals as major renewable resources for food, functional molecules, and materials as well as for bioenergy. We use a dual approach matching numerous production options (technology push) with the wide range of requested and needed end‐products in a bio‐based society (market pull or reversed engineering). The approach is based on the enlarged concept of biorefining, taking into account global and local requirements and trends. Hence, on one hand, it focuses on large‐scale, main stream production, thus following traditional supply chain methodologies with additional attention to the utilization of co‐ and by‐products (visualized as branches of a tree). On the other hand, it is centered on value‐added, small‐scale production of a wide range of cereal constituents for a wide range of end‐products (visualized as a complex network). In both cases, the innovation needs and research questions are highlighted in view of the diverse local and global challenges. © 2013 Society of Chemical Industry and John Wiley & Sons, Ltd